Pain Catastrophizing and Anxiety are Associated With Heat Pain Perception in a Community Sample of Adults With Chronic Pain. Issue 10 (October 2016) - Terry, Marisa J.; Moeschler, Susan M.; Hoelzer, Bryan C.; Hooten, W. Michael
Abstract : Background: The principle aim of this study was to investigate the associations between heat pain (HP) perception, pain catastrophizing, and pain-related anxiety in a heterogenous cohort of community-dwelling adults with chronic pain admitted to a 3-week outpatient pain rehabilitation program. Methods: All adults consecutively admitted to an outpatient pain rehabilitation program from July 2009 through January 2011 were eligible for study recruitment (n=574). Upon admission, patients completed the Pain Catastrophizing Scale (PCS), the short version of the Pain Anxiety Symptoms Scale (PASS-20), and HP perception was assessed using a standardized quantitative sensory testing (QST) method of levels. Results: Greater PCS scores were significantly correlated with lower standardized values of HP threshold (HP 0.5) ( P =0.006) and tolerance (HP 5) ( P =0.003). In a multiple variable model adjusted for demographic and clinical factors known to influence HP perception, every 10-point increase in the PCS was associated with a −0.124 point change in HP 0.5 ( P =0.014) and a −0.142 change in HP 5 ( P =0.014) indicating that participants with higher PCS scores had lower HP thresholds and tolerances, respectively. Similarly, greater PASS-20 scores significantly correlated with lower standardized values of HP 0.5 and HP 5. In a multiple variable model, every 10-point increase in the PASS-20 was associated with a −0.084 point change in HP 0.5 ( P =0.005) and a −0.116 point change in HP 5 ( P =0.001) indicating that participants with higher PASS-20 scores had lower HP thresholds and tolerances, respectively. Conclusions: The findings of this study extend the use of a standardized method for assessing HP in a heterogenous sample of adults with chronic pain. Although pain catastrophizing shares significant variance with pain-related anxiety, our findings suggest that either measure would be appropriate for use in future studies that incorporate the QST method of levels.